Realistic Mathematics Education (RME): Pendekatan Pendidikan Matematika dalam Konsep dan Realitas - ifada nofikasari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Teaching methods is always developed to make students became easily to understand the lesson. One of the developing methods tries to maka students can apply scientific theories to the real life. In this way, mathematics as pure science gets much attention to be developed. The most fundamental question is how students can utilize mathematics which initially in the form of concept as a formula which can be used in solving problem of life. Realistic Mathematics Education (RME) developed by Freudenthal Instute is a method which harmonize betweeen mathematics concept with reality. Keywords: mathematics, reality, concept, and RME.